2022
DOI: 10.1002/advs.202201834
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Wave Variable Nanotheranostic Agents for Dual‐Mode Imaging‐Guided Photo‐Induced Triple‐Therapy for Cancer

Abstract: Photothermal therapy (PTT) is a promising strategy for cancer treatment, but its clinical application relies heavily on accurate tumor positioning and effective combination. Nanotheranostics has shown superior application in precise tumor positioning and treatment, bringing potential opportunities for developing novel PTT-based therapies. Here, a nanotheranostic agent is proposed to enhance magnetic resonance imaging (MRI)/ near-infrared fluorescence imaging (NIRFI) imaging-guided photo-induced triple-therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Under this enhanced imaging guidance, the tumor sites were irradiated with NIR light. Thermal-enhanced drug release and thermal-induced damage resulted in a high tumor inhibition rate of 79.81 ± 5.30% (Figure 12 B) 196 .…”
Section: State-of-the-art Advances In Stimuli-activatable Nanomedicin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Under this enhanced imaging guidance, the tumor sites were irradiated with NIR light. Thermal-enhanced drug release and thermal-induced damage resulted in a high tumor inhibition rate of 79.81 ± 5.30% (Figure 12 B) 196 .…”
Section: State-of-the-art Advances In Stimuli-activatable Nanomedicin...mentioning
confidence: 99%
“…b) T2WI of SIA-αTSLs incubated with/without cathepsin B. c) Intratumoral cytokines; d) ratios of CD8 + T cells to Tregs in the tumor tissue; and e) tumor weights at the endpoint of the CT26-bearing mice after different treatments. Reproduced with permission 196 . Copyright 2022 the Authors, published by Wiley-VCH.…”
Section: Figurementioning
confidence: 99%
“…Killer T cells, crucial for antitumor-specific immune responses, 95 exhibit the ability to not only cooperate with other immune cells but also directly exert an immune killing effect upon activation by tumor antigens. 96 However, TEXs directly induce apoptosis in CD8+ T cell, emerging as a significant contributor to immune suppression. 97 Research has revealed that exosomes derived from mouse head and neck tumor cell line SCCVII are rich in immunosuppressive proteins, including Fas-L, PD-L1, CD39, CD73 and COX-2.…”
Section: Texs-mediated T Cell Apoptosis Immune Suppression and Treg I...mentioning
confidence: 99%
“…But still some works have described actions of TEXs directly on T cells. Killer T cells, crucial for antitumor‐specific immune responses, 95 exhibit the ability to not only cooperate with other immune cells but also directly exert an immune killing effect upon activation by tumor antigens 96 . However, TEXs directly induce apoptosis in CD8+ T cell, emerging as a significant contributor to immune suppression 97 .…”
Section: Texs‐mediated T Cell Apoptosis Immune Suppression and Treg I...mentioning
confidence: 99%
“…Photothermal therapy (PTT), utilizing photothermal agents to increase the temperature under near-infrared (NIR) light irradiation to result in cancer cell damage, has emerged as a promising approach for cancer treatment [ 14 , 15 , 16 , 17 ]. On the other hand, the increase in cancer tissue temperature can also enhance the efficiency of the Fenton catalyst, which contributes to the faster generation of highly toxic ROS for CDT [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%